A review of Chinese species of the subgenus Paederus s. str. (Coleoptera: Staphylinidae: Paederinae) with description of a new species - Li, Xiao-Yan; Zhou, Hong-Zhang (Zootaxa, 2009)
Chinese species of the subgenus Paederus s. str. (genus Paederus Fabricius, 1775) are reviewed. Paederus (s. str.) xinjiangensis Li & Zhou, n. sp. is described from Xinjiang, Northwest China. Male genitalia and other critical characters are illustrated for five other Chinese species of the subgenus Paederus s. str., namely P. (s. str.) socius Bernhauer, 1916, P. (s. str.) coxalis Fauvel, 1895, P. (s. str.) parallelus Weise, 1877, P. pilifer (s. str.) Motschulsky, 1860 and P. (s. str.) sondaicus Fauvel, 1895. A key to the six Chinese species of Paederus s. str.. is presented and their geographical distribution in China is mapped.